The Role of Training and Continuous Development in Improving Employee Productivity and its Impact on Company Financial Performance - Yertas, Maria (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2024)
This study investigates the role of training and continuous development in enhancing employee productivity and its impact on organizational financial performance. It aims to explore how tailored training initiatives, underpinned by the Resource-Based View (RBV) and employee motivation theories, can align employee competencies with strategic business objectives. This study synthesizes findings from recent research across multiple industries using a qualitative systematic literature review. The framework integrates insights from RBV and motivational theories, focusing on the interplay between training, employee development, and organizational outcomes. Data were critically analyzed to identify patterns and gaps, emphasizing the influence of digital transformation and organizational culture on training effectiveness. The study reveals that training improves technical and soft skills, fostering employee adaptability and productivity. Digital transformation tools, such as e-learning and virtual simulations, enhance the scalability and relevance of training programs. Additionally, a supportive organizational culture amplifies the impact of training, while leadership engagement ensures alignment with strategic goals. Findings also underscore the direct correlation between productivity improvements and financial outcomes, including cost efficiency, revenue growth, and operational resilience. This research emphasizes the strategic importance of training as an investment in achieving long-term sustainability and competitiveness. Practical implications highlight the need for personalized training, technology adoption, and cultural support for continuous learning. Managers are encouraged to integrate training into broader business strategies, ensuring that development initiatives align with employee needs and organizational objectives.